2015
DOI: 10.1161/circimaging.114.002989
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phenotypes of Degenerative Myxomatous Mitral Valve Disease

Abstract: Background-Fibro-elastic deficiency (FED) and diffuse myxomatous degeneration (DMD) are phenotypes of degenerative mitral valve disease defined morphologically. Whether physiological differences in annular and valvular dynamics exist between these phenotypes remains unknown. Methods and Results-We performed triple quantitation of cardiac remodeling and of mitral regurgitation severity and of annular and valvular dimensions by real-time 3-dimensional-transesophageal-echocardiography. Forty-nine patients with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 54 publications
4
59
0
3
Order By: Relevance
“…(9) Despite comparable mitral regurgitation (MR) severity consistent with surgical selection, in addition to previously described static anatomical characteristics, namely enlarged annulus and excess valvular tissue,(5) cyclic annular dynamics are blunted in DMD and systolic leaflet area changes are reduced in FED. These findings raise the possibility of primary alterations of the mitral annulus and biomechanical differences in the leaflet tissue,(10,11) with excess distensible tissue in DMD versus relatively deficient and less extensible tissue in FED.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…(9) Despite comparable mitral regurgitation (MR) severity consistent with surgical selection, in addition to previously described static anatomical characteristics, namely enlarged annulus and excess valvular tissue,(5) cyclic annular dynamics are blunted in DMD and systolic leaflet area changes are reduced in FED. These findings raise the possibility of primary alterations of the mitral annulus and biomechanical differences in the leaflet tissue,(10,11) with excess distensible tissue in DMD versus relatively deficient and less extensible tissue in FED.…”
mentioning
confidence: 75%
“…(9) This has led the authors to the concept of valve reserve, consistent with reduced valve stiffness of myxomatous valves. (10,19) Mitral valve reserve then corresponds to the ability of stressed leaflets to be stretched by ventricular forces in systole, a passive phenomenon, a process in which the valve cells themselves would be passive.…”
Section: Valve Tissue Reserve: a Passive Or Active Process?mentioning
confidence: 98%
See 1 more Smart Citation
“…8 Insufficient leaflet remodelling relative to annular and LV dilatation resulted in reduced coaptation, which was independently associated with MR severity in patients with functional MR. Figure 1 illustrates different examples of mitral valve leaflet remodelling in patients with functional MR and patients without MR. Clavel et al used 3D transoesophageal echocardiography to evaluate 49 patients with degenerative mitral valve disease. 9 The authors demonstrated important differences in LV remodelling, annular, and valvular dimensions, associated with differences in MR severity between patients with fibro-elastic deficiency and diffuse myxomatous degeneration.…”
Section: Preamblementioning
confidence: 93%
“…Kitkungvan et al (16) postulate mechanical induction of fibrosis localized to myocardium that is under increased stress and PM traction by the prolapsing leaflets (Figure 1) (20,21). Systolic annular expansion in MVP will increase PM and myocardial stress (8,22), as evidenced by reduced basal contraction that improves with repair (23). This postulate is supported by evidence for fibroblast mechanosignaling that induces myofibro-blast transformation and extracellular matrix production (24).…”
mentioning
confidence: 99%